Introduction to Matrices with Applications in Statistics - Graybill, Franklin A. (Belmont, California: Wadsworth Publishing Company, 1969)
This book is primarily concerned with the areas of Multivariate Analysis and the Linear Model. These two topics include important areas in statistics, such as design of experiments; analysis of variance; correlation; regression; least squares; components of variance- areas that comprise a large segment of the theory and application of statistics.
Rev. ed. published as: Matrices with applications in statistics. 2nd ed. 1983.
Includes bibliographical references and index.
ne 1/03/2018
Loan
Keywords: Matrices; Linear Models (Statistics)